PENGARUH AUGMENTED PRODUCT TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN DALAM MEMBELI MOTOR YAMAHA MIO DI DEALER KENCONG JAYA MOTOR - Robustin, Tri Palupi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
This study examines the influence of augmented products at the time of purchase and after the purchase on purchase decision, customer satisfaction, and customer loyalty. This research used path analysis method. Results of this study showed that augmented products at the time of purchase and after the purchase hadsignificant influence on the purchase decision through the intervening variables of satisfaction. Keywords: Augmented Products, Customer Satisfaction, Customer Loyalty.